Strategy to Improve the Quality of Employee Performance in Greater Makassar Parking Area Companies - Berliana MS, Miftah; Akib, Haedar; Nasrullah, Muh. (ASHA Publishing, 2025)
This study aims to determine the strategy to improve employee performance in the Greater Makassar Parking Regional Company. This research is qualitative descriptive; therefore, to achieve the research objectives, data collection techniques were used, namely observation/observation, interviews, and documentation with three informants, namely the Head of the General Section, the Head of the Finance Section, and the Head of the Management Section. The results of this study show that the strengths that can be used to improve employee performance are Human Resources (HR) which includes employee characteristics such as loyalty or loyalty in work so that they can know the duties of each employee, employee integrity, and innovations carried out by employees to continue to issue innovative ideas. Weaknesses in improving employee performance are age factors that will affect the performance of technology and coordination with related stakeholders, and there can be miscommunication between fellow employees, including in the cashier/finance department, who usually have different views and wills. The opportunity to improve employee performance is a reward. The intended reward or award is to give greetings to employees, such as enthusiasm and motivation for work. Other rewards or awards are in the form of promotions from contract employees to permanent employees, accompanied by operational costs, and there is no threat to the improvement of employee work at the Makassar City Parking Regional Company.